Experiential Education for Meaningful Learning: A Literature Study - Aswita, Dian (Universitas Serambi Mekkah, 2020)
To achieve meaningfulness in learning, learners are encouraged to take an active role in finding knowledge and building up their own experiences. Applying student-oriented learning models or involving students actively in the learning process is one approach that can be used by teachers. Experiential education is an educational philosophy that describes the educational process that provides direct experience for educators, learners and environment. This paper aims to introduce and discuss the experiential education with, two models of learning based on experiential education, they are experiential learning and service learning.Â Keywords: experiential education, experiential learning, service learning, meaningful learningÂ